2014
DOI: 10.1016/j.jssc.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transition and antiferromagnetic transition of Tb 3 RuO 7

Abstract: Magnetic properties and structural phase transition of terbium ruthenate Tb 3 RuO 7 are investigated through magnetic susceptibility, specific heat, high-temperature x-ray diffraction and differential scanning calorimetry measurements. The structural phase transition from space group P2 1 nb to Cmcm has been observed at 402 K. Tb 3 RuO 7 shows an antiferromagnetic transition at 17 K. In addition, another magnetic anomaly has been found at 10 K. Analysis of the magnetic specific heat for Tb 3 RuO 7 indicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…With increasing temperature, some diffraction lines which could not be indexed with space group C222 1 appear [for example, the diffraction lines show that above the phase transition temperature, they crystallize in the orthorhombic phase with space group Cmcm. 7),9),12),13), 31) We tried to analyze the X-ray diffraction profile measured at 1473 K first with the space group Cmcm. However, the diffraction lines could not be indexed based on the C-centered conditions.…”
Section: Sm 3 (Nb 1−x Ta X )O 7 Solid Solutionsmentioning
confidence: 99%
“…With increasing temperature, some diffraction lines which could not be indexed with space group C222 1 appear [for example, the diffraction lines show that above the phase transition temperature, they crystallize in the orthorhombic phase with space group Cmcm. 7),9),12),13), 31) We tried to analyze the X-ray diffraction profile measured at 1473 K first with the space group Cmcm. However, the diffraction lines could not be indexed based on the C-centered conditions.…”
Section: Sm 3 (Nb 1−x Ta X )O 7 Solid Solutionsmentioning
confidence: 99%
“…It has been reported that Ln 3 RuO 7 compounds are formed for Ln = La ~ Dy [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. For rare earth smaller than Dy, Ln 3 RuO 7 has not been prepared, i.e., Y 3 RuO 7 has not been obtained.…”
Section: (Pr 1-x Y X ) 3 Ruomentioning
confidence: 99%
“…Magnetic properties of compounds containing both rare earth and transition metal have attracted a great deal of interest, because they often show anomalous magnetic behavior due to interactions of unpaired 4f electrons and d electrons. Many studies have been performed, due to this unique crystal structure and possible related magnetic properties for Ln 3 MO 7 compounds (M = Mo [1][2][3], Ru [4][5][6][7][8][9][10][11][12][13][14][15][16][17], Re [18][19][20][21], Os [13,[22][23][24], and Ir [25][26][27][28]), especially for the magnetic properties of compounds containing Ru 5+ ion at the M-site because of its largest possible spin (S = 3/2) among the 4d and 5d transition metals. Among many Ln 3 MO 7 compounds, we focus our attention on the magnetic properties of Pr 3 RuO 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Another topic for Ln 3 MO 7 compounds is that ruthenium-, iridium-and osmium-containing members of the Ln 3 MO 7 family show structural phase transitions by specific heat and DSC measurements [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been performed [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][22][23][24][25][26][27][28][29][30], due to this unique crystal structure and possible related magnetic properties of Ln 3 MO 7 compounds (M = Mo, Ru, Re, Os, Ir), especially for the magnetic properties of compounds containing Ru 5? ion at the M-site because of its largest possible spin (S = 3/2) among the 4d and 5d transition metals.…”
Section: Introductionmentioning
confidence: 99%